Herramienta de evaluación de la cadena de valor en empresas del sector turístico: caso restaurantes - González Calle, María José; Maldonado-Matute, Juan Manuel; Armijos Orellana, Ana Carolina; Arteaga Ortiz, María Isabel (Pontificia Universidad Católica del Perú, 2025)
The social, economic, and cultural development of a country is closely linked to the performance of MSMEs, particularly in the gastronomic sector, due to their capacity to generate employment and stimulate tourism. This study aimed to design a value chain evaluation tool for restaurants, regarded as key actors in emerging economies. Amethodology combining the World Bank's approach and Porter's model was applied. The results led to the development of a tool structured in three stages: service production, marketing, and service provision, incorporating criteria adapted from primary and support activities. This flexible tool enables the diagnosis of business strengths andweaknesses, supporting decision-making, sectoral evaluation, and the formulation of productive development policies.

El desarrollo social, económico y cultural de un país está estrechamente vinculado al desempeño de las mipymes, particularmente del sector gastronómico, por su capacidad de generar empleo y dinamizar el turismo. El presente estudio tuvo como objetivo diseñar una herramienta de evaluación de la cadena de valor para restaurantes, considerados actores clave en economías emergentes. Se aplicó una metodología que integra el enfoque del Banco Mundial y el modelo de Porter. Los resultados permitieron obtener una herramienta estructurada en tres etapas: producción, marketing y provisión del servicio, con criterios adaptados a actividades primarias y secundarias. Esta propuesta, de carácter flexible, permite diagnosticar fortalezas y debilidades empresariales, facilitando la toma de decisiones, la evaluación sectorial y el diseño de políticas de desarrollo productivo.
Value chain assessment tool for tourism sector companies: restaurants case
Keywords: Value chain; Business management; Restaurants; Decision-making; Tourism; Cadena de valor; Gestión de empresas; Restaurantes; Toma de decisiones; Turismo; https://purl.org/pe-repo/ocde/ford#5.02.04